Muestra pictórica de la arquitectura urbana de Machala antiguo mediante técnica mixta - Rodríguez Piedra, Leonardo Saúl (2015)
The story makes her .... then he writes, achieved by studying documents. Galo Salcedo Parrales. Following the approach of the historian, teacher, rooted in the city of Machala researcher the topic of this important research proposal pictorial turn samples of ancient Machala through mixed technique is presented.